1992
DOI: 10.1086/133028
|View full text |Cite
|
Sign up to set email alerts
|

Southern spectrophotometric standards.

Abstract: We have obtained new observations of both secondary and tertiary spectrophotometric standards with the RC spectrographs and charge-coupled device (CCD) cameras on the 1.5-m and 4-m telescopes at CTIO in the wavelength range 3300-7550 Á, as well as UBV(RI) KC photometry for these stars. We have modified the monochromatic fluxes of the secondary spectrophotometric standards published by Taylor (1984) according to the new calibration of Vega provided by Hayes (1985). We have also tuned the zero point of the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
551
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(563 citation statements)
references
References 17 publications
10
551
0
2
Order By: Relevance
“…The standard stars LTT 3864, CD−32 • 9927, and EG 274 (Hamuy et al 1992(Hamuy et al , 1994 were observed to perform the flux calibration.…”
Section: Sample Selection Observations and Data Reductionmentioning
confidence: 99%
“…The standard stars LTT 3864, CD−32 • 9927, and EG 274 (Hamuy et al 1992(Hamuy et al , 1994 were observed to perform the flux calibration.…”
Section: Sample Selection Observations and Data Reductionmentioning
confidence: 99%
“…The final products of the pipeline were 2D wavelength calibrated spectra; our own IDL scripts were used thereafter to collapse the spectra in the spatial direction and obtain our final 1D-spectra. The standard star LTT 3218 (Hamuy et al 1992(Hamuy et al , 1994 was observed to perform the flux calibration and was also fully reduced with the pipeline. The flux calibration and radial velocity correction were performed using the standard procedures with IRAF 1 (Tody 1993).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…An overview of the CN observations, along with the geometric circumstances, is presented in Table 1. Exposures were ranging from 300 to 1,200 s. Observations of standard stars (Hamuy et al 1992(Hamuy et al , 1994 were performed to calibrate the flux in the comet images.…”
Section: Observations and Data Reductionmentioning
confidence: 99%